Internacionalização da questão colonial portuguesa: contributos das Conferências de Solidariedade - Silva, Edgar (Lusitania sacra, 2025)
In its different stages, especially in the second half of the 1960s and the first years of 1970, the dynamics of the internationalization of the problem of Portuguese colonialism in Africa gradually weakened the Estado Novo, causing Portugal’s political and diplomatic isolation, and contributed for the gestation of a broader critical consciousness in Portuguese society regarding the colonial war and the colonial system. Among the various anti-colonial movements promoted around the world, we will analyze, correlatively, the connection between Italian anti-colonialism and the anti-colonial movements based in Portugal and the crucial phases that made Italian anti-colonialism become a prominent movement of social and political transformation.